2004
DOI: 10.1046/j.0269-8463.2004.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutrient enrichment on growth, photosynthesis and hydraulic conductance of dwarf mangroves in Panamá

Abstract: Summary1. Dwarf stands of the mangrove Rhizophora mangle L. are extensive in the Caribbean. We fertilized dwarf trees in Almirante Bay, Bocas del Toro Province, north-eastern Panamá with nitrogen (N) and phosphorus (P) to determine (1) if growth limitations are due to nutrient deficiency; and (2) what morphological and/or physiological factors underlie nutrient limitations to growth. 2. Shoot growth was 10-fold when fertilized with P and twofold with N fertilization, indicating that stunted growth of these man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(130 citation statements)
references
References 61 publications
14
112
4
Order By: Relevance
“…We assessed the nutrient status of mangrove stands in the Red Sea by examining the concentrations of nitrogen, phosphorous and iron, the nutrients most often reported to limit mangrove growth (Feller, 1995;Koch and Snedaker, 1997;Feller et al, 2003a,b;Lovelock et al, 2004Lovelock et al, , 2006Naidoo, 2009;Alongi, 2011). We analyzed nutrient concentrations in mature leaves as well as the stoichiometric ratios of the nutrients to carbon.…”
Section: Nutrient Status In Central Red Sea Mangrove Standsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed the nutrient status of mangrove stands in the Red Sea by examining the concentrations of nitrogen, phosphorous and iron, the nutrients most often reported to limit mangrove growth (Feller, 1995;Koch and Snedaker, 1997;Feller et al, 2003a,b;Lovelock et al, 2004Lovelock et al, , 2006Naidoo, 2009;Alongi, 2011). We analyzed nutrient concentrations in mature leaves as well as the stoichiometric ratios of the nutrients to carbon.…”
Section: Nutrient Status In Central Red Sea Mangrove Standsmentioning
confidence: 99%
“…Indeed, low availability of nitrogen, phosphorus, and iron has been suggested as the cause for the absence of mangroves along shorelines that are otherwise suitable for mangrove growth (Sato et al, 2011). Mangrove fertilization experiments have demonstrated site-specific nutrient limitation of nitrogen and phosphorous (Feller, 1995;Koch and Snedaker, 1997;Feller et al, 2003a,b;Lovelock et al, 2004Lovelock et al, , 2006Naidoo, 2009;Alongi, 2011), whereas an experimental study conducted on mangroves in north Queensland, Australia, demonstrated iron deficiency (Alongi, 2010). Previous work has not considered these three nutrients together, which is the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N and P limitations may be directly linked to soil elevation and nutrients inputs frequencies by tides or river along the existing zonation [49][50][51]. Mangrove trees on river banks and on the shoreline can form a strong and dense fringing stand, while mangroves developing at higher elevations usually form dwarf stands [52] as it is the case in New Caledonia.…”
Section: Distribution and Speciation Of Limited Key Nutrients: Nitrogmentioning
confidence: 99%
“…At Bocas, fringe and scrub sites were located on three islands (San Cristobal, Solarte, Isla Popa) in Almirante Bay and the Chiriqui Lagoon in a vast network of mangrove islands and mainland peninsulas covering approximately 2,885 km 2 (De Croz, 1993;Guzman and Guevara, 1998;Guzman et al, 2005;Lovelock et al, 2004Lovelock et al, , 2005. Here, mangroves occurred adjacent to tropical rainforests and grew on peat approximately 5 m deep atop ancient coral reef limestone (Phillips and Bustin, 1996;Phillips et al, 1997).…”
Section: Site Descriptionsmentioning
confidence: 99%